Оценка эффективности методик и диагностики и корригирования профессионально важных качеств будущих пилотов - Кушнир, О. А. (НТУ "ХПИ", 2009)
In the article the method of diagnostics and correction professionally of important qualities of future pilots is described by facilities of surface preparation, and also motion and results of experimental estimation of its efficiency.
Keywords: авиационные катастрофы; воздушные суда; летный состав; подготовка пилотов; летные учебные заведения